KOEFISIEN PERPINDAHAN PANAS KONVEKSI PADA PEMISAHAN FRAKSI RINGAN MINYAK PELUMAS BEKAS - Tunjung Wahyu Widayati; Zubaidi Achmad (Eksergi, 2008)
Lubricant oil has límited time in its using. After ín that time, the oìl has been not aplicated so ít hasto be substìtuted with the another one. By forward wíth transportation, there wìll be pollution in environment. Inholding that problems, so the renewable processing used lubrícant oil is needed to be more ecommíc product. The process was done ín the separating equipment that was being heated 200-250"C wíth some pnæess ptameters.The parameters were 0.061 -0.0389 m/sec in flow rate, 170-230 degree C in the feeding temperature, 0.11 - 0.07 m in ã diameter of separation equipment, 77 -95.5'C in the diference temperature wíth in oíl and equipment wall. The feed from feed tank was flowed by pass heater and than its in to separation equipment. The product was dístilate, were analyzed in physic characterìzatíon í.e., specific gravity, viscosity, colour ASTM and flash point. The rafinate þottom product, heavy fractÍon, was put ín to feeding tank. The rafinøt was analyzed fisic characterization i.e., specítìc gratity, flash point, fire poínt¡ kinematic, viscosíty and viscosity índex. The rafinate analysis was done after the process was stopped.